Copper(II) complexes with an arylhydrazone of methyl 2-cyanoacetate as effective catalysts in the microwave-assisted oxidation of cyclohexane - Jlassi, Raja (2018)
Reaction of sodium (E/Z)-2-(2-(1-cyano-2-methoxy-2-oxoethylidene) hydrazinyl) benzene-sulfonate (NaHL) with copper(II) nitrate hydrate in the presence of imidazole (im) in methanol affords [CuL(im)(H2O)] (1). Complex 1 is characterized by IR spectroscopy and ESI-MS spectrometry, elemental and single crystal X-ray crystal structural analyses. The coordination environment of the central copper(II) is nearly intermediate between ideal square-based pyramidal and trigonal bipyramidal geometry, three sites being occupied by the L2- ligand, which chelates in the O, N, O fashion, while two other sites are filled with the water and imidazole molecules. Extensive intermolecular hydrogen bonds between the L2-, water and imidazole ligands lead to a 3D supramolecular network. 1 and known Cu(II) complexes [Cu(H2O)(2)L]center dot H2O (2), [Cu(H2O)(py)L]center dot H2O (3) and [Cu-3(mu(3)-OH)(NO3)(CH3OH)(mu(2)-X)(3)(mu(2)-HL)] (4) act as effective catalysts in the oxidation of cyclohexane to cyclohexanol and cyclohexanone, using low power microwave (MW) irradiation, under mild conditions. Without a promoter, the activity of the catalyst reached a turnover number of 1.44 x 10(3) and a turnover frequency of 1.98 x 10(3) h(-1), after 2 h, at 50 degrees C. (C) 2017 Elsevier B.V. All rights reserved.